Alternating current porcelain insulator and preparation method thereof
By using raw materials such as modified kaolin and advanced process processing, AC porcelain insulators with umbrella wrapping structure are prepared, which solves the problem of insufficient mechanical strength and insulation performance of traditional insulators, achieves higher mechanical strength and insulation effects, and enhances the safety and stability of the power system.
Patent Information
- Application Number
- CN202411841803.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-14
AI Technical Summary
Traditional AC porcelain insulators have shortcomings in mechanical properties and insulation properties, limited mechanical strength, easy to break and damage, and poor insulation effect, prone to local discharge and leakage problems, affecting the safety and stability of the power system.
Using modified kaolin, nano-zirconium boride, hexagonal boron nitride, rare earth-doped zirconium silicate, composite binder and flux as raw materials, AC porcelain insulators with umbrella skirt structure are prepared through electron beam irradiation treatment and high-temperature calcination, to improve their mechanical strength and insulation properties.
It significantly improves the mechanical strength and insulation performance of AC porcelain insulators, reduces the risk of rupture and damage, enhances the insulation effect, and improves the safety and stability of the power system.
Smart Images

Figure BDA0005188133170000101 
Figure BDA0005188133170000111 
Figure BDA0005188133170000121
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of insulator preparation, and in particular to an AC porcelain insulator and a preparation method thereof. Background Art
[0002] In the field of power transmission and distribution of power systems, AC porcelain insulators play a vital role. They can effectively support and insulate transmission lines and ensure the safe and stable transmission of electricity. With the continuous development of the power industry and the increasing requirements for power supply reliability, higher standards are also put forward for the performance of AC porcelain insulators.
[0003] Traditional AC porcelain insulators have gradually exposed some shortcomings in practical applications. On the one hand, in terms of mechanical properties, some existing porcelain insulators have limited mechanical strength. Under the long-term effects of conductor tension, wind loads and other external forces, they are prone to cracking and damage, which not only affects the service life of the insulators themselves, but may also cause transmission line failures and threaten the normal operation of the power system. For example, when some insulators encounter strong winds in bad weather or changes in line tension, they cannot effectively resist external forces, causing structural damage and leading to power outages.
[0004] On the other hand, in terms of insulation performance, the insulation effect of traditional porcelain insulators needs to be improved. Due to the limitations of factors such as raw materials and preparation processes, the internal crystal structure is not ideal and the impurity content is not accurately controlled, which may cause problems such as partial discharge and reduced insulation performance in high-voltage environments, reducing the safety and stability of power transmission. Moreover, during the production process, some existing preparation processes are difficult to ensure the sufficiency and uniformity of raw material mixing, which will also affect the overall performance of the final product and lead to uneven product quality.
[0005] In addition, the existing porcelain insulator production process also has shortcomings in controlling the sintering temperature and molding quality of the green body. Either the sintering temperature is high, which increases the production cost, or the green body after molding is prone to defects, affecting the performance and appearance quality of the finished product. Summary of the invention
[0006] In view of this, the present invention proposes an AC porcelain insulator and a preparation method thereof to solve the above problems.
[0007] The technical solution of the present invention is implemented as follows: an AC porcelain insulator: the AC porcelain insulator is made by glazing, firing and gluing a green body, wherein the green body comprises the following raw materials in parts by weight: 40-50 parts of modified kaolin, 10-15 parts of nano zirconium boride, 8-12 parts of hexagonal boron nitride, 5-8 parts of rare earth-doped zirconium silicate, 6-10 parts of composite binder and 3-5 parts of flux; the average particle size of the nano zirconium boride is 50-100nm; the shape of the green body is an umbrella skirt structure, the number of umbrella skirts is 3-5, the height difference between adjacent umbrella skirts is distributed according to a rule of gradually increasing from top to bottom, the height difference range is between 5-10mm, and a chamfer with a radius of 2-3mm is provided at the edge of the umbrella skirt.
[0008] Furthermore, the green body comprises the following raw materials in parts by weight: 45 parts of modified kaolin, 13 parts of nano-zirconium boride, 10 parts of hexagonal boron nitride, 7 parts of rare earth-doped zirconium silicate, 8 parts of composite binder, and 4 parts of flux.
[0009] Furthermore, the modification method of the modified kaolin is to calcine the kaolin at 500-600°C for 2-4 hours, then crush and screen the kaolin with a mesh size of 200-300 to remove impurities and make the kaolin particles more uniform, improve the irradiation modification effect, and then place it in an electron beam irradiation device with an electron beam energy of 1.2-1.5 MeV, an electron beam current intensity of 3-5 mA, an irradiation dose of 50-80 kGy, and an irradiation time of 3-5 hours. After the irradiation is completed, the kaolin is placed in an oven at 80-100°C for 1-2 hours. The treated kaolin crystal structure produces directional lattice distortion, which improves the mechanical strength of the green body and improves the insulation performance.
[0010] Furthermore, the rare earth element in the rare earth doped zirconium silicate is yttrium, and the doping amount is 3%-5% of the total mass of zirconium silicate in terms of yttrium oxide. Specifically, zirconium silicate powder with a purity of not less than 95% and an average particle size of 1-5 μm is selected as the basic raw material, and then yttrium oxide powder with a particle size of 0.5-2 μm is taken, and dried in an oven at a temperature of 120-150°C for 3-4 hours, and the two powders are mixed and ground at a speed of 200-300 rpm for 2-4 hours, and then high-temperature calcined, heated to 800-1000°C at a rate of 5-8°C / min, and kept warm for the first time for 1-3h, and then heated to 1200-1300°C at a heating rate of 3-5°C / min, kept warm at this temperature for 3-5h, and cooled to room temperature after completion to obtain rare earth doped zirconium silicate. It is used to refine the grains and improve the insulation properties of the green body.
[0011] Furthermore, during the calcination process, argon gas with a purity of more than 99.9% is introduced as a protective gas, and the gas flow rate is controlled at 10-20 L / min to prevent the raw materials from being oxidized at high temperatures, which would affect the doping effect and the quality of the final product.
[0012] Furthermore, the composite binder is composed of polyvinyl butyral, sodium alginate and polyethylene glycol diacrylate in a mass ratio of 2-5:1-3:1 to ensure the molding performance of the green body.
[0013] Furthermore, the flux is a mixture of sodium fluorosilicate and zinc borate in a mass ratio of 1:1-3, which helps to reduce the sintering temperature of the green body.
[0014] Furthermore, a method for preparing an AC porcelain insulator comprises the following steps:
[0015] S1, mixing and slurrying: weigh the above raw materials according to weight, add them into a high-speed mixer, add deionized water, and stir and mix at a speed of 800-1000 rpm for 30-45 minutes to obtain slurry;
[0016] S2, iron removal: pour the slurry into a magnetic separator, set the magnetic field strength at 0.1-0.2T, obtain slurry I, and then continue to pour it into a magnetic separator, set the magnetic field strength at 0.8-1.2T, obtain slurry II, the flow rate of the slurry is 1-3cm / s, filter and centrifuge to remove moisture from the slurry, and then dry it in an oven at a temperature of 100-120°C for 2-4h to reduce the moisture content to 5-10%;
[0017] S3, granulation molding: add ammonium bicarbonate to the mixture after iron removal and stir for 10-15 minutes, the amount of ammonium bicarbonate added is 2.5-5% of the mass of the mixture, transfer to a granulator for granulation, the granulation particle size is controlled at 0.5-1mm, and then put into a mold, and adopt cold isostatic pressing process for green body molding, the molding pressure is 150-200MPa, and the pressure holding time is 5-8min.
[0018] S4. Surface treatment: After the green body is demoulded, it is glazed, fired and glued.
[0019] Furthermore, the mass concentration of the slurry of S1 is 20-40%.
[0020] Furthermore, the temperature in the S1 high-speed mixer is controlled at 30-40° C., and during the stirring and mixing process, ultrasonic oscillation treatment is performed every 10-15 minutes, the ultrasonic power is 500-800 W, and the oscillation time is 2-4 minutes to promote more thorough mixing of the raw materials.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] First, in terms of mechanical properties, the use of specific raw materials, specially modified kaolin and reasonable shed structure design can achieve excellent mechanical properties, reduce the risk of rupture and damage, extend service life, and effectively ensure the stability of power system operation. Secondly, irradiation treatment helps to optimize the microstructure inside kaolin and reduce the influence of crystal defects and impurities on electronic conduction. When applied to the production of AC porcelain insulators, this structural optimization can effectively inhibit the migration of electrons, so that the insulator can better block current under high voltage environment, reduce the probability of leakage, partial discharge and other phenomena, and thus improve the insulation performance of the insulator; at the same time, the rare earth-doped zirconium silicate in the raw material is prepared by rigorous process, the grain is refined, and the insulation performance of the green body is improved, so that the insulator can maintain a good insulation state under high voltage environment, reduce partial discharge, and enhance the safety of power transmission. Furthermore, the composite binder ensures a good forming effect of the green body, and the flux reduces the sintering temperature, which not only saves energy and controls costs, but also avoids the degradation of raw material performance, which is conducive to improving the overall quality of the product. At the same time, the speed, concentration, temperature and ultrasonic vibration are controlled during the mixing and pulping process to ensure that the raw materials are fully and evenly mixed, thereby improving the consistency and stability of product performance. In addition, the magnetic field strength and flow rate are set in stages during the iron removal process to efficiently remove iron. During granulation and molding, various parameters are precisely controlled to ensure molding quality and dimensional accuracy. The synergistic effect of multiple links effectively improves the comprehensive performance of the product and better meets the high standards of the power system for AC porcelain insulators. DETAILED DESCRIPTION
[0023] In order to better understand the technical content of the present invention, specific embodiments are provided below to further illustrate the present invention.
[0024] Unless otherwise specified, the experimental methods used in the embodiments of the present invention are all conventional methods.
[0025] Unless otherwise specified, the materials, reagents, etc. used in the embodiments of the present invention can be obtained from commercial sources.
[0026] Example 1
[0027] An AC porcelain insulator: the AC porcelain insulator is made by glazing, firing and gluing a green body, wherein the green body comprises the following raw materials in parts by weight: 40 parts of modified kaolin, 10 parts of nano zirconium boride, 8 parts of hexagonal boron nitride, 5 parts of rare earth-doped zirconium silicate, 6 parts of composite binder and 3 parts of flux;
[0028] The modification method of the modified kaolin is to calcine the kaolin at 500°C for 2 hours, then crush and sieve the kaolin with a sieve mesh of 200 to remove impurities and make the kaolin particles more uniform, improve the irradiation modification effect, and then place it in an electron beam irradiation device with an electron beam energy of 1.2MeV, an electron beam current intensity of 3mA, an irradiation dose of 50kGy, and an irradiation time of 3h. After the irradiation is completed, it is placed in an oven at 80°C for 1 hour. The treated kaolin crystal structure produces directional lattice distortion, which improves the mechanical strength of the green body and improves the insulation performance;
[0029] The average particle size of the nano zirconium boride is 50 nm;
[0030] The rare earth element in the rare earth-doped zirconium silicate is yttrium, and the doping amount is 3% of the total mass of zirconium silicate in terms of yttrium oxide. Specifically, zirconium silicate powder with a purity of not less than 95% and an average particle size of 1 μm is selected as the basic raw material, and then yttrium oxide powder with a particle size of 0.5 μm is taken, and dried in an oven at a temperature of 120°C for 3 hours, and the two powders are mixed and ground at a speed of 200 rpm for 2 hours, and then high-temperature calcination is performed, and the temperature is increased to 800°C at a rate of 5°C / min, and the first heat preservation is performed for 1 hour, and the temperature is continued to be increased to 1200°C at a rate of 3°C / min, and the temperature is kept at this temperature for 3 hours. During the calcination process, argon gas with a purity of more than 99.9% is introduced as a protective gas, and the gas flow rate is controlled at 10L / min. After completion, it is cooled to room temperature to obtain rare earth-doped zirconium silicate;
[0031] The composite binder is composed of polyvinyl butyral, sodium alginate and polyethylene glycol diacrylate in a mass ratio of 2:1:1 to ensure the molding performance of the green body;
[0032] The flux is a mixture of sodium fluorosilicate and zinc borate in a mass ratio of 1:1-3, which helps to reduce the sintering temperature of the green body.
[0033] Example 2
[0034] An AC porcelain insulator: the AC porcelain insulator is made by glazing, firing and gluing a green body, wherein the green body comprises the following raw materials in parts by weight: 50 parts of modified kaolin, 15 parts of nano zirconium boride, 12 parts of hexagonal boron nitride, 8 parts of rare earth-doped zirconium silicate, 10 parts of a composite binder and 5 parts of a flux;
[0035] The modification method of the modified kaolin is to calcine the kaolin at 600°C for 4 hours, then crush and sieve the kaolin with a sieve mesh of 300 to remove impurities and make the kaolin particles more uniform, improve the irradiation modification effect, and then place it in an electron beam irradiation device with an electron beam energy of 1.5MeV, an electron beam current intensity of 5mA, an irradiation dose of 80kGy, and an irradiation time of 5h. After the irradiation is completed, it is placed in an oven at 100°C for 2 hours. The treated kaolin crystal structure produces directional lattice distortion, which improves the mechanical strength of the green body and improves the insulation performance;
[0036] The average particle size of the nano zirconium boride is 100 nm;
[0037] The rare earth element in the rare earth-doped zirconium silicate is yttrium, and the doping amount is 5% of the total mass of zirconium silicate in terms of yttrium oxide. Specifically, zirconium silicate powder with a purity of not less than 95% and an average particle size of 5μm is selected as the basic raw material, and then yttrium oxide powder with a particle size of 2μm is taken and dried in an oven at a temperature of 120-150°C for 4 hours, and the two powders are mixed and ground at a speed of 300rpm for 4 hours, and then high-temperature calcination is performed, and the temperature is raised to 1000°C at a rate of 8°C / min, and the first heat preservation is performed for 3h, and the temperature is continued to be raised to 1300°C at a heating rate of 5°C / min, and the temperature is kept at this temperature for 5h. During the calcination process, argon gas with a purity of more than 99.9% is introduced as a protective gas, and the gas flow rate is controlled at 20L / min. After completion, it is cooled to room temperature to obtain rare earth-doped zirconium silicate;
[0038] The composite binder is composed of polyvinyl butyral, sodium alginate and polyethylene glycol diacrylate in a mass ratio of 5:3:1 to ensure the molding performance of the green body;
[0039] The flux is a mixture of sodium fluorosilicate and zinc borate in a mass ratio of 1:3, which helps to reduce the sintering temperature of the green body.
[0040] Example 3
[0041] An AC porcelain insulator: the AC porcelain insulator is made by glazing, firing and gluing a green body, wherein the green body comprises the following raw materials in parts by weight: 45 parts of modified kaolin, 13 parts of nano zirconium boride, 10 parts of hexagonal boron nitride, 7 parts of rare earth-doped zirconium silicate, 8 parts of composite binder and 4 parts of flux;
[0042] The modification method of the modified kaolin is to calcine the kaolin at 550°C for 3 hours, then crush and sieve the kaolin with a sieve mesh of 250 to remove impurities and make the kaolin particles more uniform, improve the irradiation modification effect, and then place it in an electron beam irradiation device with an electron beam energy of 1.3MeV, an electron beam current intensity of 4mA, an irradiation dose of 70kGy, and an irradiation time of 4h. After the irradiation is completed, it is placed in an oven at 80-100°C for 1-2 hours. The treated kaolin crystal structure produces directional lattice distortion, which improves the mechanical strength of the green body and improves the insulation performance;
[0043] The average particle size of the nano zirconium boride is 80 nm;
[0044] The rare earth element in the rare earth-doped zirconium silicate is yttrium, and the doping amount is 4% of the total mass of zirconium silicate in terms of yttrium oxide. Specifically, zirconium silicate powder with a purity of not less than 95% and an average particle size of 3 μm is selected as the basic raw material, and then yttrium oxide powder with a particle size of 1.5 μm is taken and dried in an oven at a temperature of 135°C for 3 hours. The two powders are mixed and ground at a speed of 250 rpm for 3 hours, and then high-temperature calcination is performed, and the temperature is raised to 900°C at a rate of 7°C / min. The first heat preservation is performed for 2 hours, and the temperature is continued to be raised to 1200°C at a heating rate of 4°C / min. It is kept at this temperature for 4 hours. During the calcination process, argon gas with a purity of more than 99.9% is introduced as a protective gas, and the gas flow rate is controlled at 15L / min. After completion, it is cooled to room temperature to obtain rare earth-doped zirconium silicate;
[0045] The composite binder is composed of polyvinyl butyral, sodium alginate and polyethylene glycol diacrylate in a mass ratio of 2-5:1-3:1 to ensure the molding performance of the green body;
[0046] The flux is a mixture of sodium fluorosilicate and zinc borate in a mass ratio of 1:2, which helps to reduce the sintering temperature of the green body;
[0047] The above examples 1-3 adopt the following preparation method:
[0048] S1. Mixing and slurrying: weigh the above raw materials according to weight parts and add them into a high-speed mixer, add deionized water at the same time, control the temperature at 35°C, stir and mix at a speed of 900rpm for 40min, and during the stirring and mixing process, perform ultrasonic oscillation treatment every 12min, the ultrasonic power is 700W, and the oscillation time is 3min, to obtain a slurry with a mass concentration of 30%;
[0049] S2, iron removal: pour the slurry into a magnetic separator with the magnetic field strength set at 0.15T to obtain slurry I, and then continue to pour it into a magnetic separator with the magnetic field strength set at 1.0T to obtain slurry II. The flow rate of the slurry is 2cm / s. Filter and centrifuge to remove moisture from the slurry, and then dry it in an oven at 110°C for 3h to reduce the moisture content to 8%;
[0050] S3, granulation molding: add ammonium bicarbonate to the mixture after iron removal and stir for 12 minutes, the amount of addition is 4% of the mass of the mixture, transfer to a granulator for granulation, the granulation particle size is controlled at 0.8mm, and then put into a mold, and adopt cold isostatic pressing process for green body molding, the molding pressure is 180MPa, and the pressure holding time is 7min.
[0051] S4. Surface treatment: After the green body is demoulded, it is glazed, fired and glued.
[0052] Example 4
[0053] An AC porcelain insulator: the AC porcelain insulator is made by glazing, firing and gluing a green body, wherein the green body comprises the following raw materials in parts by weight: 45 parts of modified kaolin, 13 parts of nano zirconium boride, 10 parts of hexagonal boron nitride, 7 parts of rare earth-doped zirconium silicate, 8 parts of composite binder and 4 parts of flux;
[0054] The modification method of the modified kaolin is to calcine the kaolin at 550°C for 3 hours, then crush and sieve the kaolin with a sieve mesh of 250 to remove impurities and make the kaolin particles more uniform, improve the irradiation modification effect, and then place it in an electron beam irradiation device with an electron beam energy of 1.3MeV, an electron beam current intensity of 4mA, an irradiation dose of 70kGy, and an irradiation time of 4h. After the irradiation is completed, it is placed in an oven at 80-100°C for 1-2 hours. The treated kaolin crystal structure produces directional lattice distortion, which improves the mechanical strength of the green body and improves the insulation performance;
[0055] The average particle size of the nano zirconium boride is 80 nm;
[0056] The rare earth element in the rare earth-doped zirconium silicate is yttrium, and the doping amount is 4% of the total mass of zirconium silicate in terms of yttrium oxide. Specifically, zirconium silicate powder with a purity of not less than 95% and an average particle size of 3 μm is selected as the basic raw material, and then yttrium oxide powder with a particle size of 1.5 μm is taken and dried in an oven at a temperature of 135°C for 3 hours. The two powders are mixed and ground at a speed of 250 rpm for 3 hours, and then high-temperature calcination is performed, and the temperature is raised to 900°C at a rate of 7°C / min. The first heat preservation is performed for 2 hours, and the temperature is continued to be raised to 1200°C at a heating rate of 4°C / min. It is kept at this temperature for 4 hours. During the calcination process, argon gas with a purity of more than 99.9% is introduced as a protective gas, and the gas flow rate is controlled at 15L / min. After completion, it is cooled to room temperature to obtain rare earth-doped zirconium silicate;
[0057] The composite binder is composed of polyvinyl butyral, sodium alginate and polyethylene glycol diacrylate in a mass ratio of 2-5:1-3:1 to ensure the molding performance of the green body;
[0058] The flux is a mixture of sodium fluorosilicate and zinc borate in a mass ratio of 1:2, which helps to reduce the sintering temperature of the green body;
[0059] The above-mentioned Example 4 adopts the following preparation method:
[0060] S1, mixing and slurrying: weigh the above raw materials according to weight parts, add them into a high-speed mixer, add deionized water at the same time, stir and mix at a speed of 800 rpm for 30 minutes to obtain slurry;
[0061] S2, iron removal: pour the slurry into a magnetic separator, control the temperature at 30°C, set the magnetic field strength at 0.1T, obtain slurry I, and then continue to pour it into the magnetic separator, set the magnetic field strength at 0.8T, obtain slurry II, the flow rate of the slurry is 1cm / s, and ultrasonic oscillation treatment is performed every 10min, the ultrasonic power is 500W, and the oscillation time is 2min. Filter and centrifuge to remove moisture from the slurry, and then dry it in an oven at 100°C for 2h to reduce the moisture content to 5%;
[0062] S3, granulation molding: add ammonium bicarbonate to the mixture after iron removal and stir for 10 minutes. The amount of ammonium bicarbonate added is 2.5% of the mass of the mixture. Transfer it to a granulator for granulation. The granulation particle size is controlled at 0.5 mm. Then put it into a mold and use cold isostatic pressing technology to form the green body. The molding pressure is 150 MPa and the pressure holding time is 5 minutes.
[0063] S4. Surface treatment: After the green body is demoulded, it is glazed, fired and glued.
[0064] Example 5
[0065] An AC porcelain insulator: the AC porcelain insulator is made by glazing, firing and gluing a green body, wherein the green body comprises the following raw materials in parts by weight: 45 parts of modified kaolin, 13 parts of nano zirconium boride, 10 parts of hexagonal boron nitride, 7 parts of rare earth-doped zirconium silicate, 8 parts of composite binder and 4 parts of flux;
[0066] The modification method of the modified kaolin is to calcine the kaolin at 550°C for 3 hours, then crush and sieve the kaolin with a sieve mesh of 250 to remove impurities and make the kaolin particles more uniform, improve the irradiation modification effect, and then place it in an electron beam irradiation device with an electron beam energy of 1.3MeV, an electron beam current intensity of 4mA, an irradiation dose of 70kGy, and an irradiation time of 4h. After the irradiation is completed, it is placed in an oven at 80-100°C for 1-2 hours. The treated kaolin crystal structure produces directional lattice distortion, which improves the mechanical strength of the green body and improves the insulation performance;
[0067] The average particle size of the nano zirconium boride is 80 nm;
[0068] The rare earth element in the rare earth-doped zirconium silicate is yttrium, and the doping amount is 4% of the total mass of zirconium silicate in terms of yttrium oxide. Specifically, zirconium silicate powder with a purity of not less than 95% and an average particle size of 3 μm is selected as the basic raw material, and then yttrium oxide powder with a particle size of 1.5 μm is taken and dried in an oven at a temperature of 135°C for 3 hours. The two powders are mixed and ground at a speed of 250 rpm for 3 hours, and then high-temperature calcination is performed, and the temperature is raised to 900°C at a rate of 7°C / min. The first heat preservation is performed for 2 hours, and the temperature is continued to be raised to 1200°C at a heating rate of 4°C / min. It is kept at this temperature for 4 hours. During the calcination process, argon gas with a purity of more than 99.9% is introduced as a protective gas, and the gas flow rate is controlled at 15L / min. After completion, it is cooled to room temperature to obtain rare earth-doped zirconium silicate;
[0069] The composite binder is composed of polyvinyl butyral, sodium alginate and polyethylene glycol diacrylate in a mass ratio of 2-5:1-3:1 to ensure the molding performance of the green body;
[0070] The flux is a mixture of sodium fluorosilicate and zinc borate in a mass ratio of 1:2, which helps to reduce the sintering temperature of the green body;
[0071] The above-mentioned Example 5 adopts the following preparation method:
[0072] S1, mixing and slurrying: weigh the above raw materials according to weight parts, add them into a high-speed mixer, add deionized water at the same time, stir and mix at a speed of 1000 rpm for 45 minutes to obtain slurry;
[0073] S2, iron removal: pour the slurry into a magnetic separator, control the temperature at 40°C, set the magnetic field strength at 0.2T, obtain slurry I, and then continue to pour it into the magnetic separator, set the magnetic field strength at 1.2T, obtain slurry II, the flow rate of the slurry is 3cm / s, and ultrasonic oscillation treatment is performed every 15min, the ultrasonic power is 800W, and the oscillation time is 4min. Filter and centrifuge to remove moisture from the slurry, and then dry it in an oven at a temperature of 120°C for 4h to reduce the moisture content to 5-10%;
[0074] S3, granulation molding: add ammonium bicarbonate to the mixture after iron removal and stir for 15 minutes. The amount of ammonium bicarbonate added is 5% of the mass of the mixture. Transfer it to a granulator for granulation. The granulation particle size is controlled at 1 mm. Then put it into a mold and use cold isostatic pressing technology to form the green body. The molding pressure is 200 MPa and the pressure holding time is 8 minutes.
[0075] S4. Surface treatment: After the green body is demoulded, it is glazed, fired and glued.
[0076] Comparative Example 1
[0077] The difference between this comparative example and Example 3 is that the green body comprises the following raw materials in parts by weight: 35 parts of modified kaolin, 20 parts of nano-zirconium boride, 5 parts of hexagonal boron nitride, 3 parts of rare earth-doped zirconium silicate, 12 parts of composite binder, and 8 parts of flux.
[0078] Comparative Example 2
[0079] The difference between this comparative example and Example 3 is that the kaolin used as the raw material of the green body is not modified.
[0080] Comparative Example 3
[0081] The difference between this comparative example and Example 3 is that the zirconium silicate of the raw material of the green body is not doped with rare earth.
[0082] Comparative Example 4
[0083] The difference between this comparative example and Example 3 is that no iron removal step is performed in the preparation method.
[0084] 1. Electrical performance test
[0085] 1. Insulation resistance test: test standard GB / T1001.1-2021;
[0086] 2. AC withstand voltage test: GB / T16927.1-2011; expressed as the maximum test voltage that can pass, and the test time is set according to the standard;
[0087] 3. Distributed voltage test: GB / T16927.1-2011; take the sample value of the average distributed voltage of a single insulator in the insulator string;
[0088] 4. Leakage current detection: GB / T1001.2-2021; measured at the same operating voltage of 110kV;
[0089] Test results:
[0090] Table 1:
[0091]
[0092]
[0093] The AC porcelain insulators produced by the embodiment group showed better performance than the comparative group in all aspects, indicating that the insulators of the embodiment have certain advantages in design, raw material selection or manufacturing process, making them more reliable and stable in electrical performance, and more suitable for use in occasions such as transmission lines with high requirements for electrical insulation.
[0094] 2. Mechanical properties test
[0095] 1. Tensile strength test: Install the two ends of the AC insulator samples of the above-mentioned embodiments 1-5 and comparative examples 1-4 on the upper and lower clamps of the tensile testing machine respectively, and ensure that the clamps can firmly clamp the samples and that the tensile force can be evenly applied along the axis of the insulator to avoid eccentric force; start the tensile testing machine and slowly apply the tensile force at a specified rate until the insulator sample is damaged. During the test, the testing machine automatically records the magnitude of the tensile force and the elongation of the sample.
[0096] 2. Bending strength test: Place the sample on the support blade, adjust the distance between the support blades, make the length of the sample outside the support blade is 10mm, and ensure that the two support blades are in the same plane and parallel to each other, and at the same time make the loading blade be located in the middle of the two support blades; turn on the insulator ceramic bending tester, and load at an average speed of 10-50N / s until the sample is destroyed. During the loading process, be careful not to impact the sample when the loading blade contacts it, so as to avoid causing additional damage to the sample and affecting the test results. Record the maximum load when the sample is destroyed;
[0097] 3. Torsion strength test: Install the AC porcelain insulator sample on the fixture of the torsion tester, usually using a three-jaw chuck or two-way tightening type and other suitable torsion attachments to ensure that the sample can be firmly fixed and will not loosen or slip during the torsion process. Start the torsion tester, output torque through the servo motor and reduction system, and apply torque to the sample at the specified torsion speed. The torsion speed is controlled within the range of 1R / min.
[0098] Test results:
[0099] Table 2:
[0100]
[0101]
[0102] Based on the above analysis of tensile strength, bending strength and torsional strength, it can be seen that the AC porcelain insulators represented by the embodiments are overall superior to the comparative group in terms of mechanical properties, and Example 3 stands out by virtue of its outstanding performance in these three key indicators and has more excellent mechanical properties.
[0103] The comparison between Example 3 and Comparative Example 1 shows that the insulator green body raw material can improve various mechanical performance indicators under a specific ratio, so that it can better cope with the complex mechanical stress conditions in actual operation.
[0104] Compared with Comparative Example 2, Example 3 uses kaolin irradiated with a high-energy electron beam at a specific irradiation dose to produce directional lattice distortion in its crystal structure. Compared with traditional untreated kaolin, this can better improve the performance of the porcelain insulator green body and lay the foundation for improving the mechanical strength and insulation performance of the green body.
[0105] Compared with Comparative Example 3, Example 3 uses rare earth yttrium-doped zirconium silicate and accurately controls the doping amount, which can refine the grains and further improve the insulation performance of the green body. This is a performance optimization of traditional zirconium silicate materials, making it more suitable for the production of high-performance porcelain insulators.
[0106] Compared with Example 4, Example 3 can significantly reduce the iron content in the porcelain insulator through iron removal treatment, improve its insulation performance, and at the same time, reduce the number of stress concentration points formed by iron impurities in the porcelain insulator, thereby improving the mechanical strength and durability of the porcelain insulator.
[0107] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. An AC porcelain insulator, characterized in that: The AC porcelain insulator is made by glazing, firing and gluing a green body, wherein the green body comprises the following raw materials in parts by weight: 40-50 parts of modified kaolin, 10-15 parts of nano zirconium boride, 8-12 parts of hexagonal boron nitride, 5-8 parts of rare earth-doped zirconium silicate, 6-10 parts of a composite binder and 3-5 parts of a flux; the average particle size of the nano zirconium boride is 50-100nm; the shape of the green body is an umbrella skirt structure, the number of umbrella skirts is 3-5, the height difference between adjacent umbrella skirts is distributed in a regular pattern of gradually increasing from the top to the bottom, the height difference range is between 5-10mm, and a chamfer with a radius of 2-3mm is provided at the edge of the umbrella skirt.
2. An AC porcelain insulator as claimed in claim 1, characterized in that: The green body comprises the following raw materials in parts by weight: 45 parts of modified kaolin, 13 parts of nano zirconium boride, 10 parts of hexagonal boron nitride, 7 parts of rare earth-doped zirconium silicate, 8 parts of composite binder and 4 parts of flux.
3. An AC porcelain insulator as claimed in claim 1, characterized in that: The modification method of the modified kaolin is to calcine the kaolin at 500-600° C. for 2-4 hours, then crush and sieve the kaolin to remove impurities, and then place it in an electron beam irradiation device with an electron beam energy of 1.2-1.5 MeV, an electron beam current intensity of 3-5 mA, an irradiation dose of 50-80 kGy, and an irradiation time of 3-5 hours. After the irradiation is completed, the kaolin is placed in an oven at 80-100° C. for 1-2 hours.
4. An AC porcelain insulator as claimed in claim 1, characterized in that: The rare earth element in the rare earth doped zirconium silicate is yttrium, and the doping amount is 3%-5% of the total mass of the zirconium silicate in terms of yttrium oxide. Specifically, zirconium silicate powder with a purity of not less than 95% and an average particle size of 1-5 μm is selected as the basic raw material, and then yttrium oxide powder with a particle size of 0.5-2 μm is taken, and dried in an oven at a temperature of 120-150° C. for 3-4 hours, and the two powders are mixed and ground at a speed of 200-300 rpm for 2-4 hours, and then high-temperature calcination is performed, and the temperature is increased to 800-1000° C. at a rate of 5-8° C. / min, and the first heat preservation is performed for 1-3 hours, and the temperature is continued to be increased to 1200-1300° C. at a heating rate of 3-5° C. / min, and the temperature is kept at this temperature for 3-5 hours. After completion, it is cooled to room temperature to obtain rare earth doped zirconium silicate.
5. An AC porcelain insulator as claimed in claim 5, characterized in that: During the calcination process, argon gas with a purity of more than 99.9% is introduced as a protective gas, and the gas flow rate is controlled at 10-20 L / min.
6. An AC porcelain insulator as claimed in claim 1, characterized in that: The composite adhesive consists of polyvinyl butyral, sodium alginate and polyethylene glycol diacrylate in a mass ratio of 2-5:1-3:
1.
7. An AC porcelain insulator as claimed in claim 1, characterized in that: The flux is a mixture of sodium fluorosilicate and zinc borate in a mass ratio of 1:1-3.
8. The method for preparing an AC porcelain insulator according to claim 1, characterized in that: The following steps are involved: S1, mixing and slurrying: weigh the above raw materials according to weight parts, add them into a high-speed mixer, add deionized water at the same time, stir and mix at a speed of 800-1000 rpm for 30-45 minutes to obtain slurry; S2, iron removal: pour the slurry into a magnetic separator, set the magnetic field strength at 0.1-0.2T, obtain slurry I, and then continue to pour it into a magnetic separator, set the magnetic field strength at 0.8-1.2T, obtain slurry II, the flow rate of the slurry is 1-3cm / s, filter and centrifuge to remove moisture from the slurry, and then dry it in an oven at a temperature of 100-120°C for 2-4h to reduce the moisture content to 5-10%; S3, granulation molding: add ammonium bicarbonate to the mixture after iron removal and stir for 10-15 minutes, the amount of ammonium bicarbonate added is 2.5-5% of the mass of the mixture, transfer to a granulator for granulation, the granulation particle size is controlled at 0.5-1mm, and then put into a mold, and adopt cold isostatic pressing process for green body molding, the molding pressure is 150-200MPa, and the pressure holding time is 5-8min. S4. Surface treatment: After the green body is demoulded, it is glazed, fired and glued.
9. The method for preparing an AC porcelain insulator according to claim 7, characterized in that: The mass concentration of the slurry S1 is 20-40%.
10. The method for preparing an AC porcelain insulator according to claim 7, characterized in that: The temperature in the S1 high-speed mixer is controlled at 30-40° C., and during the stirring and mixing process, ultrasonic oscillation treatment is performed every 10-15 minutes, the ultrasonic power is 500-800W, and the oscillation time is 2-4 minutes.
Citation Information
Cited By
Porcelain insulator and production process thereof
CN120496969A